Diversely polarised antenna‐array‐based narrowband/wideband beamforming via polarisational reconstruction matrix inversion. Issue 3 (1st May 2018) - Lu, Ying; Xu, Yougen; Huang, Yulin; Liu, Zhiwen
Abstract : The problem of beamforming using diversely polarised antenna array is addressed in the study. With the attempt to avoid signal cancellation caused by very small snapshot number, and/or look direction error and/or polarisation mismatch, the polarisational reconstruction matrix inversion based beamformer is developed for both the narrowband and wideband cases. The major contribution is on the reconstruction of the narrowband case interference‐plus‐noise covariance matrix and wideband case focused interference‐plus‐noise covariance matrix, for the cases of both completely polarised and partially or randomly polarised interferences, by the rank‐1 and rank‐2 spatial spectrum techniques, respectively. The performance of the proposed beamformer, against small snapshot number, look direction error, polarisation mismatch, and focusing error, was evaluated by extensive simulations, and compared with the polarisational extensions of some existing popular polarisation insensitive beamformers, in terms of the output signal‐to‐interference‐plus‐noise ratio values and the experimental deviation of the signal‐of‐interest (SOI) estimate. The influences of direction difference between SOI and interference, degrees of polarisation of SOI and interference, and integrating range for reconstruction on beamforming performance are also studied.